Fracture mechanic analysis of multiple edge cracks in a finite plate using kerf to emulate crack interaction - Ahmad Faizal Annuar (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2015)
The main intention of this study attempts to simulate and find a possibility to replace subsequent crack interaction to primary crack with kerf, incise in Electric Discharge Machining (WEDM) wire cut, by evaluating the longitudinal stress distribution component. Current regional technology of WEDM permits kerf gap machining at 0.050mm. This research, focuses on emulating two parallel edge cracks' interaction as initial attempt to prove that kerf provides similar interaction on primary crack's SIF. Through simulation using ABAQUS Computer Aided Engineering (CAE), values of non-uniform stress distributions produced by kerf within the potential primary crack region was analysed and compared to non-uniform stress distributions that produced by a crack as validation.